Redox Flow Battery Sebagai Perangkat Penyimpanan Energi - Septiani Silitonga; Ricky Therisno; Charles S.P. Manurung; Parulian Siagian; Yong Song Chen; Richard A M Napitupulu (SPROCKET JOURNAL OF MECHANICAL ENGINEERING, 2021)
Energy storage such as vanadium redox flow batteries (VRFB) has increased to store renewable energy resources in the last decade. However, the unbalanced crossover level of vanadium is often a major constraint which has a significant impact on battery capacity and life cycle in long-term operation. Performing an asymmetric electrolyte volume is one of many ways to solve this problem. The different volumes on the positive and negative sides were analyzed to see their effect in suppressing the decrease in VRFB capacity. With the result of the optimal electrolyte excess ratio, long-term cycle performance was carried out to investigate the reduction in capacity of VRFBs.